What approach to development in the Cape Winelands : an identification and exploration into urban form - planning for future growth and change in the Cape Winelands region - De Wet, Barend Frederik Lutz (School of Architecture, Planning and Geomatics, 2017)
The urban form of many South African cities is often considered inequitable, fragmented, and unsustainable. Modernist planning ideology and Apartheid social policies left cities with a highly inefficient urban form and structure that reflects fragmentation, separation and a high degree of lateral urban sprawl. These ideologies have led to the development of mono-functional settlements which are often environmentally sterile. This dissertation aims to find a new approach to development in the Cape Winelands region. It investigates the role of urban form, and proposes a new model for the integration of wilderness, rural and urban space. The study is motivated by the research question: what approach to development in the Cape Winelands? The focus is on the inequitable and inefficient urban structure and form, as well as urban growth management strategies for the emerging global challenges. High levels of growth which is accompanied by increasing levels of poverty, unemployment and inequality enable the critical action for a new approach toward planning. These challenges is also causing uncontrolled urban development that is encroaching into valuable agricultural land and sensitive environmental areas. Moreover the struggle for densification in the core of Stellenbosch - heritage constraints is contributing to the uneven distribution of densities that lead to an unsustainable urban form and use of space. The dissertation seeks to direct public and private capital investment, and to channel growth, but equally protecting wilderness and valuable arable land.